A systematic review of cranioplasty material toxicity in human subjects - Las, David Emmanuel; Verwilghen, Denis; Mommaerts, Maurice Yves (Journal of cranio-maxillo-facial surgery, 2021)
Local and systemic toxic reactions to implanted materials can result in morbidities. However, little is reported about cranioplasty implants. Therefore, we performed a systematic review on the toxicity of different materials used for cranioplasty implants. A systematic search was conducted by browsing the Pubmed, Embase, and Cochrane Library databases. All human studies that identified toxic (aseptic) reactions to any types of material used as cranioplasty implants or onplants, published up to January 1, 2019, were included in the review. Nineteen studies were identified. Collectively, 36 patients endured some type of toxic reaction to an implanted material. Eleven studies presented several types of toxicity for PMMA cranioplasties in several tissue types. One article highlighted the risk of neurotoxicity for PMMA cranioplasty. Three articles presented toxic reactions to calcium phosphate and titanium implants. Three additional articles presented toxic reactions to PEEK, polypropylene-polyester, and polyethylene. All materials currently used for cranioplasty showed occasional toxicity and morbidities. Therefore, none can be considered completely biologically inert. We found that aseptic inflammatory reactions have been underreported in the literature due to a high incidence of infections with questionable evidence.